Developing The Competitiveness Model of The Palm Oil-Based Fatty Acid and Fatty Alcohol Industry in Indonesia Using Porter’s Diamond Cluster Competitiveness Model - Toni Yoyo; Vivin Hanitha; Hendra Hendra (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The definition of oleochemicals is a source of chemicals made from natural oils or fats, derived from animals or plants. Oleochemicals derived from palm oil are fatty alchohols and acid which are currently widely used. The purpose of this research is to develop model of diamond clusters from Porter to see the competitiveness of industries based on fatty acids and fatty alcohols derived from palm oil in Indonesia. From this research, data is generated showing that based on the model used, namely the industrial competitiveness model, there are several sub-factors with "good" status and other sub-factors with "bad" status. In shaping the competitiveness of the palm oil-based fatty acid and fatty alcohol industry in Indonesia, the â€œgoodâ€ sub-factor is used. while the weakness that comes from the "bad" sub-factor can reduce the competitiveness of the palm oil-based fatty acid and alcohol, so it is necessary to maximize the good sub-factors.